Ellipses Quick Check
1 of 41 of 4 Items
Question
When is an ellipsis used?(1 point)
Responses
to correct or delete information
to correct or delete information
to show where a thought ends
to show where a thought ends
to indicate a change in subject
to indicate a change in subject
to indicate a pause or an omission
to indicate a pause or an omission
11 answers
to indicate a pause or an omission
What does an omission indicate in a sentence? (1 point)
Responses
something corrected
something corrected
a pause
a pause
something left out
something left out
a suggestion
Responses
something corrected
something corrected
a pause
a pause
something left out
something left out
a suggestion
something left out
In a fictional text, an ellipsis is most likely used for which purpose? (1 point)
Responses
to indicate an omission
to indicate an omission
to show that a new scene is beginning
to show that a new scene is beginning
to show that a character is confused
to show that a character is confused
to indicate a long pause
Responses
to indicate an omission
to indicate an omission
to show that a new scene is beginning
to show that a new scene is beginning
to show that a character is confused
to show that a character is confused
to indicate a long pause
to indicate a long pause
Why would an author use an ellipsis to omit words from a quote?(1 point)
Responses
to create suspense
to create suspense
to leave out unnecessary information
to leave out unnecessary information
to break up the text
to break up the text
to add in additional thoughts
Responses
to create suspense
to create suspense
to leave out unnecessary information
to leave out unnecessary information
to break up the text
to break up the text
to add in additional thoughts
to leave out unnecessary information
Solve for the given variable. [Click Here for Help Video]
(1 point)
−16z−19=−12z+9
z=
(1 point)
−16z−19=−12z+9
z=
To solve for z in the equation −16z−19=−12z+9, we can start by isolating the variable terms on one side of the equation.
Adding 12z to both sides, we get:
−16z−12z−19=−12z+12z+9
Simplifying the equation:
−28z−19=9
Next, we can isolate the constant term by adding 19 to both sides:
−28z−19+19=9+19
Simplifying further:
−28z=28
To solve for z, we divide both sides by −28:
−28z/−28 = 28/−28
Simplifying:
z = -1
Therefore, the value of z in the given equation is -1.
Adding 12z to both sides, we get:
−16z−12z−19=−12z+12z+9
Simplifying the equation:
−28z−19=9
Next, we can isolate the constant term by adding 19 to both sides:
−28z−19+19=9+19
Simplifying further:
−28z=28
To solve for z, we divide both sides by −28:
−28z/−28 = 28/−28
Simplifying:
z = -1
Therefore, the value of z in the given equation is -1.
−16z−19=−12z+9
z=
z=
To solve for z in the equation −16z−19=−12z+9, we can start by isolating the variable terms on one side of the equation.
Adding 12z to both sides, we get:
−16z−12z−19=−12z+12z+9
Combining like terms on both sides:
−28z−19=9
Next, we can isolate the constant term by adding 19 to both sides:
−28z−19+19=9+19
Simplifying further:
−28z=28
To solve for z, we divide both sides by −28:
z = 28/−28
Simplifying:
z = -1
Therefore, the value of z in the given equation is -1.
Adding 12z to both sides, we get:
−16z−12z−19=−12z+12z+9
Combining like terms on both sides:
−28z−19=9
Next, we can isolate the constant term by adding 19 to both sides:
−28z−19+19=9+19
Simplifying further:
−28z=28
To solve for z, we divide both sides by −28:
z = 28/−28
Simplifying:
z = -1
Therefore, the value of z in the given equation is -1.